Modification of Starch with Amylosucrase: Methods, Physicochemical Properties and Health Implications - Dewi, Angela Myrra Puspita; Tethool, Eduard Fransisco (Universitas Atma Jaya Yogyakarta, 2024)
Amylosucrase is a transglucosylase enzyme that utilizes sucrose as a substrate to produce α-1,4 glucan (amylose-like polymer). Modification of starch with Amylosucrase can increase the degree of polymerization, degree of crystallinity, heat stability, and increase the proportion of slow digestible starch (SDS) and resistant starch (RS). Thus, Amylosucrase (ASase) modified starch has enormous potential to be developed in the food industry because the consumption of ASase modified starch can improve insulin sensitivity and reduce blood glucose response, making it suitable for consumption by people with Diabetes Mellitus. In addition, consumption of ASase-modified starch also has the potential to prevent obesity and improve blood lipid profile.